2019
DOI: 10.1111/edt.12503
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire‐based survey for the evaluation of the knowledge level of primary school teachers on first‐aid management of traumatic dental injuries in Athens, Greece

Abstract: Background/AimSchool teachers can play an important role in improving the prognosis of traumatized teeth of school children through immediate onsite management or on time referral to healthcare providers. In Greece where the research in the field of dental traumatology is very limited, this issue is of utmost importance. The aim of this study was to evaluate the knowledge level of Greek primary school teachers and their attitude with regard to emergency first‐aid management of traumatic dental injuries (TDI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(110 citation statements)
references
References 32 publications
9
96
1
4
Order By: Relevance
“…In the present study, insufficient knowledge was also shown by preschool education and teacher’s education students. There are numerous studies confirming a low level of knowledge about dental trauma among preschool education teachers/students and teachers’ education students /school teachers in Croatia and other countries ( 5 - 7 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, insufficient knowledge was also shown by preschool education and teacher’s education students. There are numerous studies confirming a low level of knowledge about dental trauma among preschool education teachers/students and teachers’ education students /school teachers in Croatia and other countries ( 5 - 7 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the included studies had been published within last decade. [11][12][13][14][15][16][17][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Most of them (17) were conducted in Asia, 11,13,14,16,17,[20][21][22][23][24][25]27,29,[32][33][34][35] two in South America, 15,31 two in Africa, 26,30 one each in Europe 12 and Australia. 28 Among the countries, India had the highest number (7) 11,16,23,27,…”
Section: Re Sultsmentioning
confidence: 99%
“…11 These principles can be learned and executed at the time of a TDI by the first responders such as children/ adolescents, school teachers, coaches, parents and police officers to reduce suffering of the injured individual and to improve the prognosis of the injured tooth. [11][12][13] Since most TDI occur during school hours or in school-related sports activities, it is imperative to assess the level of awareness of school teachers for the prevention and emergency management of TDI. 11 Several researchers have tried to do this through studies done in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, they all should know what to do with an avulsed tooth at the scene of accident. Previous studies have reported a low level of knowledge about rst aid management of dental trauma including avulsion [7][8][9].…”
Section: Introductionmentioning
confidence: 99%